The influence of two-factor theory on employee retention: The mediating role of organizational citizenship behavior and the moderating role of leader-member exchange in business management - Amodia, Justine B.; Visitacion, Roberto H. (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: Globally, firms face a crucial problem with employee retention since it has a big impact on their sustainability, profitability, and productivity. The goal of this study is to propose management interventions that may be implemented to improve employee retention of medical representatives by assessing the Two-factor variables that affect it using Partial Least Squared Structual Equation Modeling. Methods: As part of the research approach, a thorough analysis of existing literatures and studies on employee retention, including scholarly journals was conducted. In the context of investigated study, the findings indicate that employee retention is significantly and positively influenced by factors such as compensation and benefits and promotion. The mediation effect of Organizational Citizenship Behavior to the relationship of compensation and benefits and employee retention; and promotion and employee retention is found not significant. Findings: The results of the study also showed that Leader-Member Exchange positively and significantly moderates the relationship between coworker relations and employee retention; and working conditions and employee retention. Conclusion: The study concludes that employee retention is a complex problem that needs a comprehensive approach to effectively solve. Although other Two-factor variables did not demonstrate a strong correlation with employee retention, this does not imply that they are not meaningful. It is possible that in the circumstances of the study under investigation, promotions, pay, and benefits are more strongly associated with employee retention. To learn more about this connection, future research may examine what constitutes high-quality LMX and how organizations might promote a favorable culture between leaders and employees. Novelty/Originality of this Study: This study contributes to understanding the specific factors influencing employee retention in the context of medical representatives, with an emphasis on the moderating role of Leader-Member Exchange and its effect on coworker relations and working conditions.